Repositioning Islamic Banking Education in Aceh: Insights from Student Perceptions and Global Best Practices - Diana, Sari; Friwarti, Sri Dwi; Maulida, Ulvia; Mellyan (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2025)
Purpose – This research aims to explore the perceptions of prospective students in choosing the Islamic Banking Study Program at STAIN Teungku Dirundeng Meulaboh and to explore the factors influencing their views on the program. Method – The research employs a mixed-method approach, involving 267 students from the West-South Aceh region as respondents. Findings –.The results indicate that 193 prospective students (73.40%) are interested in pursuing higher education, while 71 the students (26,6%) have no intention of continuing their studies. Furthermore, 207 prospective students (77.5%) were unaware of the Islamic Banking Study Program at STAIN Meulaboh, whereas 60 (22.5%) acknowledged knowing about the program. In terms of interest, 167 prospective students (62.5%) were not interested in enrolling in the Islamic Banking Study Program, while 100 (37.5%) expressed their interest. Several factors influencing their perceptions include experience, faculty qualifications, and cost. Practical implications – Understanding the factors affecting prospective students' perceptions can help institutions, particularly STAIN Teungku Dirundeng Meulaboh, develop strategies such as create engaging content for social media platform and build strong alumni networks to improve awareness and attract more interest in the Islamic Banking Study Program. Originality/value – This study provides insights into islamic banking study program, prospective students’ behavior, Islamic finance education, and mixed-method research